2013
DOI: 10.1149/2.022311jss
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low Temperature Silicon Nitride Spacer for High-k Metal Gate Integration

Abstract: As transistor dimension becomes smaller and with the switch to high-k metal gate (HKMG) integration, the need for a sidewall protection layer that is conformal yet meets the low thermal budget requirement becomes critical. In this work, we evaluated PEALD SiN as spacer material in comparison to PECVD SiN, at two different stresses (compressive and tensile) and two different deposition temperatures. Material characterization reveals that PEALD SiN has lower hydrogen impurities, higher density and better resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 11 publications
2
46
1
Order By: Relevance
“…The residual stress of this film was found to be compressive in nature ( Figure 15 d) similar to that reported previously for SiN x deposited at a comparable temperature. 54 The nature of the stress for SiN x is unlike the tensile stresses observed earlier for the transition metal compounds deposited without biasing but similar to the compressive stress obtained for SiO x . An N/Si ratio of 1.4 ± 0.1 was observed for this film ( Table 4 ) indicating the formation of nearly stoichiometric Si 3 N 4 (N/Si ratio of 1.33) for deposition without any biasing.…”
Section: Resultssupporting
confidence: 80%
“…The residual stress of this film was found to be compressive in nature ( Figure 15 d) similar to that reported previously for SiN x deposited at a comparable temperature. 54 The nature of the stress for SiN x is unlike the tensile stresses observed earlier for the transition metal compounds deposited without biasing but similar to the compressive stress obtained for SiO x . An N/Si ratio of 1.4 ± 0.1 was observed for this film ( Table 4 ) indicating the formation of nearly stoichiometric Si 3 N 4 (N/Si ratio of 1.33) for deposition without any biasing.…”
Section: Resultssupporting
confidence: 80%
“…Provine et al AIP Advances 6, 065012 (2016) exhibit low WERs in dilute aqueous HF, have been reported utilizing both trisilylamine (TSA) 9 and bis(tert-butylamino)silane (BTBAS). 10,14,15 To improve thin film properties (crystallinity, morphology, density, trap density) rapid thermal annealing (RTA) is commonly used.…”
Section: -2mentioning
confidence: 99%
“…Plasma enhanced chemical vapor deposition can deposit films at temperatures lower than that by using thermal LPCVD. Unfortunately, this leads to poor step coverage and low film quality [3,15,16]. To address issues related to conformality, the ALD technique has been studied extensively [19 26]; ALD is a cyclic process that offers atomic scale thickness control of the material that is being deposited.…”
Section: Introductionmentioning
confidence: 99%